Molecular Circuitry of the SUMO (Small Ubiquitin-like Modifier) Pathway in Controlling Sumoylation Homeostasis and Suppressing Genome Rearrangements - de Albuquerque, Claudio Ponte (J Biol Chem, 2016)
Small ubiquitin-like modifier (SUMO) E3 ligases are known to have a major role in preventing gross chromosomal rearrangements (GCRs); however, relatively little is known about the role of SUMO isopeptidases in genome maintenance and their role in controlling intracellular sumoylation homeostasis. Here we show the SUMO isopeptidase Ulp2 in Saccharomyces cerevisiae does not prevent the accumulation of GCRs, and interestingly, its loss causes subunit-specific changes of sumoylated minichromosome maintenance (MCM) helicase in addition to drastic accumulation of sumoylated nucleolar RENT and inner kinetochore complexes. In contrast, loss of Ulp1 or its mis-localization from the nuclear periphery causes substantial accumulations of GCRs and elevated sumoylation of most proteins except for Ulp2 targets. Interestingly, the E3 ligase Mms21, which has a major role in genome maintenance, preferentially controls the sumoylation of Mcm3 during DNA replication. These findings reveal distinct roles for Ulp1 and Ulp2 in controlling homeostasis of intracellular sumoylation and show that sumoylation of MCM is controlled in a subunit-specific and cell cycle dependent manner.